PENINGKATAN MINAT BELAJAR BAHASA INGGRIS BAGI SISWA-SISWI MA NURUL HUDA PAOWAN MELALUI ENGLISH CLUB - Firqo Amelia; Ahmad Yusuf Firdaus; Sufil Lailiyah (INTEGRITAS : Jurnal Pengabdian, 2017)
This program overcomes the lack of students’ interest in learning English, as one of the problems faced by MA Nurul Huda Paowan. This activity is a form of effort made by University of Abdurachman Saleh Situbondo to solve the problems faced by society. This helps improve the students’ interest in learning English through extracurricular activity called English Club. Based on the preliminary observations, learning English in the classroom is less effective because many of the students in the class are not motivated to improve their skills at English. For that reason, extracurricular activity is proposed to be held and followed by students who are interested in learning English.This cummunity service is carried out for two months with three stages; preparation, assistance, and evaluation. Preparation stage is done to establish communication with the school. The emphasis in this communication period is the commitment of the school to keep running the English Club after the the service period ends. The second stage, which is assistance, is done by supervising the English Club activities four times, forming the English Club's board, and accompanying the inauguration of the board. The last stage is evaluation. That is done at the end of the service period to provide the school with inputs on the existing relevant issues and discuss the best applicable solutions.The outcomes generated from this activity are: (1) the students’ increased interest in learning English; (2)the establishment of an extracurricular activity, called English Club, in MA Nurul Huda Paowan; (3) the establishment of board of the English Club; (4) members’ knowledge of English Club management; (5) Fulfillment of some materials and instructional media supporting the English Club; and(6) an article to be published in a national journal with ISSN.